Comparison of Peroxidase Enzyme Activity and Spot Test in Soybean [Glycine max (L.) Merill] Genotypes - JAGADISH HOSAMANI; M DADLANI; MB ARUN KUMAR; IM SANTHA; A TALUKDAR; SK LAL (Seed Research, 2026)
Thirty three soybean [Glycine max (L.) Merill] genotypes, comprising 14 black seeded and 19 yellow seeded ones, were selected on the basis of their reported storability for a comparative study on peroxidase activity and validation of spot test. It was observed that though the mean peroxidase activity was higher in poor storer genotypes, it cannot clearly differentiate a good storer from the poor, and irrespective of the initial status, the peroxidase activity declines drastically during storage. The peroxidase spot test, which is used for grouping soybean varieties into positive and negative reaction groups, which is not indicative of their storability behaviour. It was also evidenced that the spot test reaction changes drastically with storage, revealing the importance of sampling only fresh/high vigour soybean seeds for peroxidase test.